Studi Kasus: Aksesbilitas Petani Kopi terhadap Kredit dari Lembaga Keuangan Bank - Sartika, Sheila Ruth; Karyani, Tuti (Politeknik Negeri Lampung, 2018)
The development of coffee plants in Indonesia shows a rapid growth to fulfill domestic and foreign needs. However, there are still farmers who have not been able to maximize their market potential by using post-harvest technology to increase value added caused by the low accessibility of farmers to farming capital.This research aims to identify accessibility of coffee farmers to financial institution and analyze the factors of credit accessibility towards bank as financial institution of coffee farmers at Kubangsari 2 Farmers Group. The research design used quantitative design with survey research technique. The research sampling used simple random sampling with 31 sample of farmers picked. The data analysis used logit regression method with SPSS 21as a statistical tools. The results show that the coffee farmers take credit accessibility to bank (41,94%), non-bank (3,23%), and non-formal financial institution (51,61%). Besides that, there is 3,23% respondents did not access credit. The result of logit regression shows the factors that effect to credit accessibility of coffee farmers is age, formal education, farming experience, number of coffee trees, and coffee farming income. Keywords: credit accesibility, farming income, logit regression